Prediksi Gempa Bumi di Yogyakarta Berdasarkan Nilai Magnitudo, Kedalaman, dan Lokasi Gempa Menggunakan Naïve Bayes - Liantoni, Febri; Mutiah Ratih Purwanti; Zahra Khalila Salsabila (PETIR, 2024)
This study focuses on earthquake prediction in Yogyakarta, Indonesia, a region prone to seismic activity due to its location on the Pacific tectonic plate. Utilizing data mining, specifically the Naïve Bayes algorithm, the research aims to assess the accuracy of earthquake strength predictions. The study employs a quantitative approach involving data collection, preprocessing, attribute selection, modeling, training, validation, and evaluation. Data from BMKG covering May 1, 2023, to July 31, 2023, is used, concentrating on magnitude, depth, and location attributes. Results indicate that Naïve Bayes can predict earthquake attributes with notable accuracy. The findings establish the viability of data mining techniques, particularly Naïve Bayes, for earthquake prediction in Yogyakarta, offering significance for earthquake preparedness and mitigation in the region. The study emphasizes the ongoing challenge of accurate earthquake prediction due to complex sub-surface interactions. Overall, this research contributes to improving earthquake resilience and reducing the impact of seismic events in Yogyakarta.